1996
DOI: 10.1084/jem.183.4.1561
|View full text |Cite
|
Sign up to set email alerts
|

Nasal administration of glutamate decarboxylase (GAD65) peptides induces Th2 responses and prevents murine insulin-dependent diabetes.

Abstract: SummaryWe previously demonstrated that a spontaneous Thl response against glutamate decarboxylase (GAD65) arises in NOD mice at four weeks in age and subsequently T cell autoimmunity spreads both intramolecularly and intermolecularly. Induction of passive tolerance to GAD65, through the inactivation of reactive T cells before the onset of autoimmunity, prevented determinant spreading and the development of insulin-dependent diabetes mellitus (IDDM). Here, we examined whether an alternative strategy, designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
245
1
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(259 citation statements)
references
References 40 publications
11
245
1
2
Order By: Relevance
“…We found that the production of IL-4 increased, whereas the production of IFN-γ decreased, indicating that the immunisation of NOD mice with rVV-GAD65 induced a Th2 immune response in an antigenspecific manner. Our finding is consistent with the results of previous reports on NOD mice treated with GAD protein systemically, nasally or orally [28,29,33,34,35] or vaccinated with GAD encoding plasmid DNA [41]. Th2 immune responses induced by rVV-GAD immunisation could play an important role in the prevention of autoimmune diabetes in this animal model.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that the production of IL-4 increased, whereas the production of IFN-γ decreased, indicating that the immunisation of NOD mice with rVV-GAD65 induced a Th2 immune response in an antigenspecific manner. Our finding is consistent with the results of previous reports on NOD mice treated with GAD protein systemically, nasally or orally [28,29,33,34,35] or vaccinated with GAD encoding plasmid DNA [41]. Th2 immune responses induced by rVV-GAD immunisation could play an important role in the prevention of autoimmune diabetes in this animal model.…”
Section: Discussionsupporting
confidence: 93%
“…In Type I diabetes, GAD and insulin have been identified as major autoantigens and tolerisation against these autoantigens has been attempted as a method for the prevention of the disease [14,32]. It has been reported that administration of purified GAD protein or peptide or insulin protein or peptide to NOD mice by a variety of routes can tolerise the T cell-mediated immune response against pancreatic beta cells, resulting in the prevention or delay of the development of insulitis and diabetes [28,29,33,34,35,36,37,38,39]. In many cases, the preventive effect was found to be associated with a Th2 shift [14,32].…”
Section: Discussionmentioning
confidence: 99%
“…T cells from diabetic but not from pre-diabetic young NOD mice proliferated in response to this peptide. Moreover, immunisation with this peptide protects NOD mice from diabetes (as immunisation with other autoantigens does [25,26]) by inducing regulatory T cells of the TH2 phenotype which are capable of preventing adoptively transferred diabetes [16]. These findings conflict with the idea that NOD beta cells are MHC class II-negative.…”
Section: Discussionmentioning
confidence: 94%
“…With the onset of periinsulitis, beta-cell-antigenspecific T cells become detectable [25,32,33]. These islet-specific T cells are of TH1 phenotype and show signs of activation [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Intervention of this cytokine imbalance by autoantigen-specific tolerance induction, by costimulation blockade or by overexpression of IL-4 could prevent diabetic progression. However, those treatments are most effective when administrated to NOD mice beginning at 2-3 wk of age [26][27][28]. In pre-diabetic NOD mice that undergo late peri-insulitis, inhibition of the Th1 cell is crucial but not sufficient to completely inhibit the disease progression.…”
mentioning
confidence: 99%